2018
DOI: 10.1002/aocs.12134
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ultrasound and Microwave to Improve the Yield and Quality of Single‐Cell Oil from Mortierella isabellina NTG1−121

Abstract: In this article, to increase the extraction efficiency and quality of single-cell oil (SCO) from Mortierella isabellina NTG 1-121 (MIN) in the SCO extraction, ultrasound in combination with microwave was applied. The best extraction conditions (microwave power 400 W; microwave time 3.7 min; ultrasonic time 40.5 min; ultrasonic power 500 W; and the material to solvent ratio 1:12.3 [w/v]) were achieved at room temperature of 25 AE5 C, using response surface methodology (RSM). Under these conditions, the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This phenomenon occurred because the microwave treatment obviously affected the external and internal structure of the samples, and heat was transferred by radiation, conduction, and convection during MAE. Zhou et al [43] reported that an explosion takes place at the cell level due to the quick rise in temperature caused by microwave radiation. In addition, the high temperature and high pressure of PLE also led to cell damage of the coffee power ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon occurred because the microwave treatment obviously affected the external and internal structure of the samples, and heat was transferred by radiation, conduction, and convection during MAE. Zhou et al [43] reported that an explosion takes place at the cell level due to the quick rise in temperature caused by microwave radiation. In addition, the high temperature and high pressure of PLE also led to cell damage of the coffee power ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhou et al. [ 36 ] an explosion occurs at the cellular level due to the rapid temperature rise generated by microwave radiation. Thus, intracellular components can diffuse into the solvent used for extraction.…”
Section: Resultsmentioning
confidence: 99%
“…[35] In the case of MAE, some irregular cavities and holes appeared due to the destruction of cell structure (Figure 2c). According to Zhou et al [36] an explosion occurs at the cellular level due to the rapid temperature rise generated by microwave radiation. Thus, intracellular components can diffuse into the solvent used for extraction.…”
Section: Microstructure Analysis By Semmentioning
confidence: 99%
“…The phenomena are responsible for damaging cell walls, releasing intracellular compounds. Zhou et al (2018) studied the efficiency of extraction and the quality of SCO from M. isabellina using ultrasound in combination with the microwave extraction method. It was observed that the combined extraction method improved the quality and yield of SCO.…”
Section: Considerations For Sco Recovery Methodsmentioning
confidence: 99%